Development of a self-management intervention for employees with complaints of the arm, neck and/or shoulder (CANS): a focus group study with experts - Hutting, Nathan (J Occup Med Toxicol, 2015)
BACKGROUND: Many people suffer from complaints of the arm, neck and/or shoulder (CANS). The complaints are persistent and there is a need for intervention programs for those with longstanding CANS. Studies suggest that a behavioural change is needed in employees with CANS. A self-management program with an add-on eHealth module might be an effective option to achieve the behavioural change needed to manage the complaints in employees with CANS. The aim of this study was to determine the content and strategies of the intervention and to gain insight into possible barriers and facilitators for implementation. Therefore, we examined the views of experts on the problems and characteristics associated with employees with CANS as well as their opinion on a self-management program consisting of self-management sessions and an eHealth module. METHODS: A qualitative study was performed consisting of three focus groups involving a total of 17 experts (with experience with CANS, self-management and/or eHealth interventions). Experts were asked their opinion about the content and requirements of a self-management program for employees with CANS, including an eHealth module. Data were analysed using qualitative data analysis. After coding, the emergent themes were used to organise the data into main categories, expressing the ideas and opinions of experts on CANS, self-management and/or eHealth interventions. RESULTS: The experts pointed out that the intervention should focus on increasing employees’ self-efficacy and empowerment, and address topics related to the possible risk factors for CANS, symptoms, work environment, social environment and personal factors. The eHealth module should be self-explanatory and attractive, and the information provided should be brief, clear and concise. CONCLUSIONS: Experts appeared to see a role for a self-management program for employees with CANS. They indicated that the combination of group sessions and eHealth can work well. Experts provided valuable information with regard to the content of the self-management intervention and the design of the eHealth module.